A glucose tolerant β-glucosidase from Thermomicrobium roseum that can hydrolyze biomass in seawater. Issue 18 (7th September 2021) - Sinha, Sushant K.; Datta, Maithili; Datta, Supratim
Abstract : A β-Glucosidase B9L147 from Thermomicrobium roseum can tolerate high concentration of glucose, ionic liquids, salts and metal ions and can hydrolyse substrate in seawater. Abstract : β-Glucosidase (EC 3.2.1.21) plays an essential role in the hydrolysis of the β-1, 4 linkage of cellobiose. Accumulated glucose during saccharification leads to the inhibition of the production of β-glucosidase, which causes an accumulation of cellobiose and inhibition of other cellulolytic enzymes. Thus, glucose tolerant and active β-glucosidase is required for the efficient saccharification of biomass. Freshwater is an essential ingredient of biotechnological processes and contributes to the environmental and economic cost of processes. Relatively few biocatalytic processes have been developed to utilize seawater, which is more abundant. Towards both the requirements, we set out to characterize a hyperthermophilic enzyme, B9L147, and evaluate its activity in seawater, and compared it with the industrial enzyme benchmarks. B9L147 from Thermomicrobium roseum was cloned and expressed in Escherichia coli . The overexpressed and purified wild-type showed a high specific activity of 280 ± 5.2 μmol min −1 mg −1 on p NPGlc when assayed at pH 7 and 84 °C. B9L147 retains at least 80% relative specific activity across a wide pH range from 5.5 to 10.0. The enzyme is glucose tolerant and remains fully active until 3 M glucose. The kinetic properties, stability, and glucose tolerance remain identical in seawater, unlike commercial enzymes. An engineered variant, V169C, showed a 15% enhanced specific activity and almost twice the half-life compared to the wild type (B9L147). Both B9L147 and V169C show very high synergistic activity when supplemented with commercial cellulases and enzymes cloned and overexpressed in our lab. To the best of our knowledge, B9L147 is the first β-glucosidase that can hydrolyze cellulose in seawater at elevated temperatures and thus may be of value for industrial applications. Our studies offer a framework for developing seawater tolerant in vitro saccharification systems for biomass hydrolysis towards the sustainable production of biofuels and chemicals from biomass.